Mini EXPLORER II: a prototype high-sensitivity PET/CT scanner for companion animal whole body and human brain scanning. (21st March 2019) - Lv, Yang; Lv, Xinyu; Liu, Weiping; Judenhofer, Martin S; Zwingenberger, Allison; Wisner, Erik; Berg, Eric; McKenney, Sarah; Leung, Edwin; Spencer, Benjamin A; Cherry, Simon R; Badawi, Ramsey D
Abstract: As part of the EXPLORER total-body positron emission tomography (PET) project, we have designed and built a high-resolution, high-sensitivity PET/CT scanner, which is expected to have excellent performance for companion animal whole body and human brain imaging. The PET component has a ring diameter of 52 cm and an axial field of view of 48.3 cm. The detector modules are composed of arrays of lutetium (yttrium) oxyorthosilicate (LYSO) crystals of dimensions 2.76 × 2.76 × 18.1 mm 3 coupled to silicon photomultipliers (SiPMs) for read-out. The CT component is a 24 detector row CT scanner with a 50 kW x-ray tube. PET system time-of-flight resolution was measured to be 409 ± 39 ps and average system energy resolution was 11.7% ± 1.5% at 511 keV. The NEMA NU2-2012 system sensitivity was found to be 52–54 kcps MBq −1 . Spatial resolution was 2.6 mm at 10 mm from the center of the FOV and 2.0 mm rods were clearly resolved on a mini-Derenzo phantom. Peak noise-equivalent count (NEC) rate, using the NEMA NU 2-2012 phantom, was measured to be 314 kcps at 9.2 kBq cc −1 . The CT scanner passed the technical components of the American College of Radiology (ACR) accreditation tests. We have also performed scans of a Hoffman brain phantom and we show images from the first canine patient imaged on this device.